2015
DOI: 10.1136/neurintsurg-2015-011927
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aneurysmal hemodynamics: evaluation of pCONus and pCANvas bifurcation aneurysm devices using DSA optical flow imaging

Abstract: BackgroundImplantation of self-expanding stents from the parent artery into the sac of a bifurcation aneurysm is regularly used to facilitate endovascular coil occlusion with the so-called waffle cone technique (WCT). Self-expanding aneurysm bridging stents like Solitaire AB, can be used; however, bifurcation devices like pCONus and pCANvas are especially designed for WCT. These devices provide additional support for coil implantation owing to intraluminal nylon fibers (pCONus) or membranes (pCANvas) covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…However, this was recently shown not to be the case. Pérez et al 22 recently demonstrated that neither a Solitaire stent placed in a waffle cone technique, nor a pCONus device resulted in increased flow into the aneurysm. Indeed, the study showed rather a mild decrease in intra-aneurysmal flow with both devices, and no significant flow-diverting effect due to the device, as has been suggested with Y stenting 23.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was recently shown not to be the case. Pérez et al 22 recently demonstrated that neither a Solitaire stent placed in a waffle cone technique, nor a pCONus device resulted in increased flow into the aneurysm. Indeed, the study showed rather a mild decrease in intra-aneurysmal flow with both devices, and no significant flow-diverting effect due to the device, as has been suggested with Y stenting 23.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 13 14 15 ] The pCONus device is a stent exclusively made for this purpose. [ 16 ] The pCONus device is a nitinol stent with distal radially flared four loops (petals) which are to be positioned at the base of the aneurysm and an additional six polyamide fibers at the distal diameter of the stent forming a barrier preventing coil prolapse into the parent vessels. The device is compatible with a 0.021 inch microcatheter, is retrievable even after complete deployment, and is detached electrolytically.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 18 ] A study on intraaneurysmal flow kinetics using DSA optical flow imaging after deployment of the pCONus device has shown no adverse increase in aneurysmal flow; on the contrary, it has shown a minimal reduction. [ 16 ] An added advantage of the device is that, in the case of aneurysm re-growth, the petals still remain at the neck of the aneurysm and facilitate coil retention within the aneurysm. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…This will inevitably result in continued flow into the aneurysm around the edges of the membrane. Although this flow may be reduced it is unlikely to be completely stopped as was suggested by the bench side studies that showed a 60% reduction in intra-aneurysmal flow [23]. This flow may also be predominantly directed around the edges of the aneurysm with relatively decreased flow centrally Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given that hemodynamics play an important role in the recanalization of aneurysms [21] and that high shear stress at the aneurysm neck is a risk factor for aneurysm recurrence [22], the natural evolution of neck bridging devices should prevent intra-aneurysmal blood flow. The flowmodifying effects were recently tested in an in vitro silicone model of a basilar tip aneurysm with a blood-mimicking fluid under pulsatile conditions [23]. Intra-aneurysmal flow was compared between the pCONus1, the Solitaire AB (Medtronic, Irvine, CA, USA) deployed in a manner that replicates the waffle cone technique, and the pCANvas.…”
Section: Discussionmentioning
confidence: 99%